The experience of living in deprived neighbourhoods for LGBT+ people: Making home in difficult circumstances. (October 2019) - Matthews, Peter; Poyner, Christopher
Research in urban studies on lesbian, gay, bisexual and trans (LGBT+) people and their housing choices has focused on economic choices and the role of exclusion, or conversely higher household disposable income, in residential location. Evidence on lived experiences has focused on residence in so-called 'gaybourhoods' with high concentrations of non-heterosexual households, or experiences within the home. Contrasting to this scholarship, in this paper we focus on LGBT+ people who live in socially rented housing in deprived neighbourhoods that are geographically, socially and economically marginal. Our evidence shows how complex experiences of exclusion for LGBT+ people, not always directly connected to their sexual or gender identity, led to individuals living in these neighbourhoods. Using the theoretical approach of housing pathways, we further suggest that these neighbourhoods offer limited affordances for wellbeing for LGBT+ individuals that need to be recognised by housing and other service providers. We also argue that mainstream housing and urban studies needs to use sexual and gender identity as a category of analysis in research so we can better understand the lived experiences of non-heterosexual individuals and households.